Wear-resistant acid-corrosion-resistant environment-friendly anti-explosion PE pipe

Through the design of multi-layer composite PE pipes, the coordinated enhancement of functionalized polyethylene and surface modification enhancement particles is optimized to optimize the combination of particle distribution and interface, and the lack of performance of traditional PE pipes in high wear, corrosion and electrostatic environments is solved, and the comprehensive improvement of wear resistance, anti-static and corrosion resistance is achieved.

CN119899446APending Publication Date: 2025-04-29SUZHOU LINGYU PLASTIC PIPE TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510166158.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional PE pipes have insufficient wear resistance in high wear environments, and have poor chemical resistance in corrosion environments such as strong acids and alkalis. The problem of static accumulation is serious, and the single-layer structure design is difficult to meet the needs of wear resistance, anti-static and corrosion resistance at the same time.

Method used

The multi-layer composite PE pipe design is adopted to enhance the synergistic enhancement of functionalized polyethylene and surface modification to enhance the particle distribution, optimize the particle distribution, and use multi-functional silane coupling agent to modify the particles to form a strong interface combination, and a three-layer structure is designed through multi-layer co-extrusion technology.

Benefits of technology

It significantly improves the wear resistance, acid and alkali corrosion resistance and explosion-proof performance of the pipe, solves the problems of insufficient interface bonding force, limited dispersion of conductive filler and single structural design, and meets the needs of complex working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899446A_ABST
    Figure CN119899446A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite pipes, and discloses a wear-resistant acid-corrosion-resistant environment-friendly anti-explosion PE pipe. The pipe adopts a multi-layer co-extrusion structural design, and comprises a wear-resistant inner layer, a reinforced middle layer and a protective outer layer. High-density polyethylene is used as a base material, silicon carbide particles and aluminum oxide particles with the surfaces subjected to multifunctional modification are combined to serve as reinforcing filler, and functional polyethylene is used as a base interface modification material, so that the problems that in a traditional pipe, particles and a base interface are low in bonding force, uneven in dispersion, prone to falling off and the like are solved. Carboxyl and unsaturated double bonds are introduced into the functionalized polyethylene through a maleic anhydride grafting technology, so that efficient chemical combination of particles and a matrix is realized, and the mechanical property and the chemical stability of the composite material are improved. The inner layer enhances wear resistance through high particle content, the middle layer provides support and corrosion resistance, and the outer layer improves weather resistance and protection performance of the pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite pipes, in particular to an environmentally friendly explosion-proof PE pipe that is wear-resistant and acid-corrosion-resistant. Background Art

[0002] Polyethylene (PE) pipes are widely used in chemical, petroleum, mining and other fields due to their excellent chemical stability and mechanical properties. However, under complex working conditions, the performance of traditional PE pipes shows obvious limitations. First, PE pipes show insufficient wear resistance in high-wear environments. In order to improve this performance, the matrix is ​​often strengthened by adding reinforcing particles such as silicon carbide and alumina. However, most particles are only added through physical mixing, which easily forms agglomeration points or uneven distribution in the matrix. Under the action of external forces, the bonding force between the particles and the matrix is ​​limited, and particles are prone to fall off, which not only fails to improve the wear resistance, but also aggravates the secondary wear.

[0003] In corrosive environments such as strong acids and alkalis, the chemical resistance of traditional pipes also faces challenges. Although polyethylene itself has certain acid and alkali resistance, the interfacial bonding strength decreases after long-term immersion in corrosive media, and the internal particles are exposed to the corrosive environment, resulting in significant degradation of material performance. Existing methods mostly blend functional resins with polyethylene to improve corrosion resistance, but due to the limited compatibility of the two, a stable anti-corrosion barrier cannot be formed. In addition, the single-layer material design has insufficient pressure buffering capacity for corrosive media and is difficult to meet long-term stability requirements.

[0004] Static electricity accumulation is another significant problem when polyethylene pipes are used in the fields of petroleum, chemical industry, etc. Traditional polyethylene materials are prone to static electricity risks when transporting flammable media due to their strong insulation. To solve this problem, the existing technology mostly adopts the method of doping conductive fillers, such as adding carbon black or metal powder. However, the dispersion effect of these conductive fillers is limited, and it is difficult to form a continuous conductive path in the matrix, resulting in low static electricity release efficiency. At the same time, a high filling amount of conductive fillers will significantly reduce the toughness of the matrix, making the pipe more brittle and not conducive to long-term use.

[0005] The traditional single-layer PE pipe design also limits the improvement of its comprehensive performance. It is difficult for a single-layer material to simultaneously meet the requirements of high wear resistance, anti-static performance, and corrosion resistance. The overall performance depends on the uniformity of the matrix material and the filler. Some studies have attempted to improve performance through functional blended materials, but due to the lack of targeted layered design, the performance of the material under complex working conditions is still unsatisfactory. For example, in a scenario where both wear resistance and anti-static performance are required, a single structural design is difficult to strike a balance between mechanical properties and electrical properties.

[0006] The existing technology for modifying PE pipes still has problems such as insufficient interface bonding, lack of targeted corrosion barrier design, limited dispersibility of conductive fillers and single structural design. In view of these problems, a multi-layer composite PE pipe is developed, which can achieve comprehensive improvement of wear resistance, anti-static and corrosion resistance through functional particle modification, multi-scale particle distribution optimization and layered structure design, meet the needs of complex working conditions, and has important technical significance. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides an environmentally friendly explosion-proof PE pipe that is wear-resistant and acid-corrosion-resistant to solve the problem.

[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: a wear-resistant, acid-corrosion-resistant, environmentally friendly explosion-proof PE pipe, which is made of the following components in parts by mass: high-density polyethylene: 60 to 75 parts; functionalized polyethylene: 5 to 10 parts; silicon carbide particles: 8 to 15 parts; alumina particles: 3 to 8 parts; silane coupling agent: 1 to 2 parts; thermal stabilizer: 0.1 to 0.3 parts; antioxidant: 0.2 to 0.5 parts; dispersant: 0.5 to 1 part.

[0009] Preferably, the functionalized polyethylene is prepared by the following method: polyethylene and maleic anhydride are mixed in a mass ratio of 90-95:2-4, 0.5%-1% by mass of an initiator is added, a grafting reaction is carried out at 170°C-200°C, the reaction time is 8 minutes-15 minutes, and then cooled and granulated.

[0010] Preferably, the silicon carbide particles include micron particles with a particle size of 1 μm to 5 μm and nanoparticles with a particle size of 50 nm to 100 nm, which are mixed in a mass ratio of 4:1.

[0011] Preferably, the alumina particles have a particle size range of 0.5 μm to 1 μm, and are surface treated after being activated by dilute nitric acid or sodium hydroxide solution.

[0012] Preferably, the silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltriethoxysilane, which are used in a mass ratio of 1:1.

[0013] Preferably, the high-density polyethylene, functionalized polyethylene, silicon carbide particles, alumina particles, silane coupling agent and additives are mixed in the mass proportion and melt-blended in a twin-screw extruder, with a melt temperature of 190°C to 230°C, a screw speed of 200rpm to 250rpm, and a residence time of 6 minutes to 10 minutes.

[0014] Preferably, the mixed materials are formed by multi-layer co-extrusion, and the PE tube is a three-layer structure, including: Inner layer: 1.0mm-1.5mm thick, composed of a mixture with a reinforcing particle content of 15%; Middle layer: 2.0mm to 3.0mm thick, composed of a mixture of functionalized polyethylene and reinforced particles; Outer layer: 0.8mm~1.5mm thick, made of high-density polyethylene.

[0015] Preferably, during the extrusion process of the three-layer structure material, the extrusion pressure is 10MPa-20MPa, the mold temperature is 200°C-240°C, and the cooling water tank temperature is 15°C-25°C.

[0016] Preferably, the surface modification of the reinforcing particles comprises the following steps: S1. Treat the reinforced particles with a dilute acid or alkaline solution to activate the particle surface and remove impurities at a temperature of 50°C to 70°C for 15 to 30 minutes; S2. Introducing bifunctional groups on the particle surface through a coupling agent, the coupling agent concentration is 1.0% to 2.0%, the reaction temperature is 60°C to 80°C, and the reaction time is 30 minutes to 60 minutes.

[0017] A method for preparing an environmentally friendly explosion-proof PE pipe that is wear-resistant and acid-corrosion-resistant, comprising the following steps: S1. After the silicon carbide particles and the aluminum oxide particles are surface activated, a silane coupling agent is added for modification to obtain surface modified particles; S2. grafting polyethylene with maleic anhydride under the action of an initiator to obtain functionalized polyethylene; S3. The high-density polyethylene, the functionalized polyethylene, the modified particles and the additives are mixed in a weight ratio and melt-blended in an extruder to obtain a composite material; S4. The composite material is extruded through a multi-layer co-extrusion device to form a three-layer structure, including an inner layer, a middle layer and an outer layer, and the PE pipe is obtained by cooling after extrusion.

[0018] The present invention provides an environmentally friendly explosion-proof PE pipe that is wear-resistant and acid-corrosion-resistant. It has the following beneficial effects: 1. The present invention successfully introduces amino and epoxy groups on the surface of silicon carbide and aluminum oxide particles by using surface activation and modification technology of bifunctional silane coupling agent. The modified particles react chemically with the carboxyl groups in the functionalized polyethylene to form a strong interface bond. Compared with the prior art solution of using only monofunctional silane coupling agent to modify the particle surface, the present invention solves the problem of weak interface bonding and easy particle shedding, and significantly improves the wear resistance.

[0019] 2. The present invention optimizes the distribution of particles in the polyethylene matrix by designing a multi-scale synergistic reinforcement structure of micron and nanoparticles. Micron particles construct a mechanical support framework, and nanoparticles fill the interface gaps to improve interface stability. Compared with the traditional single-size particle reinforcement technology, the present invention solves the stress concentration problem caused by uneven particle distribution and greatly improves the pressure resistance and dimensional stability of the material.

[0020] 3. The present invention uses functionalized polyethylene as a modified matrix, and uses maleic anhydride grafting to introduce carboxyl groups and unsaturated double bonds, thereby achieving an efficient chemical reaction between particles and the matrix. Compared with the prior art method of improving the interface strength only by physical intercalation, the present invention completely solves the secondary wear problem caused by particle shedding. At the same time, the interface reaction further improves the chemical corrosion resistance of the pipe.

[0021] 4. The present invention designs a three-layer composite structure through multi-layer co-extrusion technology, and rationally divides the functional layer, reinforcement layer and protective layer. The inner layer gives the material excellent wear resistance, the middle layer improves the compressive strength, and the outer layer provides weather resistance and protective performance. Compared with the single-layer structure design in the prior art, the present invention solves the problems of single performance and limited application scenarios, and significantly expands the applicable working conditions of the pipe. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic flow chart of the preparation steps of the environmentally friendly explosion-proof PE pipe in the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Please refer to the attached Figure 1, this technical solution designs a composite material with high-density polyethylene (HDPE) as the matrix, synergistically reinforced by functionalized polyethylene (F-PE) and surface-modified reinforcing particles (silicon carbide and aluminum oxide). The core is to optimize the interface bonding between the reinforcing particles and the matrix through surface chemical functionalization, melt blending process and multi-layer co-extrusion design, thereby significantly improving the wear resistance, acid and alkali corrosion resistance and explosion-proof performance, including high-density polyethylene (HDPE): 60% to 75%; functionalized polyethylene (F-PE): 5% to 10%; surface-modified silicon carbide particles: 8% to 15%; surface-modified aluminum oxide particles: 3% to 8%; silane coupling agent: 1% to 2%; thermal stabilizer: 0.1% to 0.3%; antioxidant: 0.2% to 0.5%; dispersant: 0.5% to 1%. The following are examples and comparative examples under the ratio of each component material: Example 1: Preparation of a highly wear-resistant, environmentally friendly and explosion-proof PE pipe.

[0025] Surface modification of enhanced particles: Silicon carbide (SiC) particles were mixed with 1μm to 5μm micron particles and 50nm to 100nm nanoparticles in a mass ratio of 4:1, added to a 5% dilute nitric acid solution, stirred for 20 minutes, and the temperature was controlled at 60°C. Then filtered and washed with deionized water until neutral. After drying, 1.5% ethanol solution of γ-aminopropyltriethoxysilane (APTESS) and γ-glycidyloxypropyltriethoxysilane (GPTESS) was added, APTESS and GPTESS were mixed in a 1:1 ratio, the temperature was 70°C, and after reacting for 40 minutes, it was taken out, washed twice with ethanol, and dried for 3 hours, and the temperature was kept at 80°C.

[0026] Preparation of functionalized polyethylene: 95 parts of high-density polyethylene and 3 parts of maleic anhydride were mixed, and 0.8 parts of diisopropylbenzene peroxide was added as an initiator, and the mixture was placed in an internal mixer for reaction at a temperature of 180°C, a rotation speed of 40 rpm, and a reaction time of 12 minutes. After cooling, the mixture was granulated for later use.

[0027] Composite blending: Ingredients: 70 parts of high-density polyethylene, 8 parts of functionalized polyethylene, 12 parts of modified silicon carbide particles, 5 parts of alumina particles (activated and modified by 5% sodium hydroxide), 1.5 parts of silane coupling agent, 0.3 parts of heat stabilizer, 0.4 parts of antioxidant, and 0.8 parts of polyethylene glycol dispersant.

[0028] The ingredients were melt blended in a twin-screw extruder, the temperature was set at 200°C to 230°C, the screw speed was 220 rpm, and the residence time was 7 minutes.

[0029] Extrusion molding: The multi-layer co-extrusion equipment produces three-layer pipes, with an inner layer thickness of 1.2mm (particle content 15%), a middle layer thickness of 2.5mm (particle content 10%), and an outer layer thickness of 1.0mm (pure high-density polyethylene). The extrusion pressure is 16MPa, the mold temperature is 220℃, the cooling water tank temperature is 20℃, and the cooling time is 15 minutes before cutting and forming.

[0030] Example 2: Preparation of a highly corrosion-resistant and explosion-proof PE pipe.

[0031] Particle modification steps: Alumina particles (particle size 0.5μm to 1μm) were added to 5% sodium hydroxide solution for 25 minutes at a reaction temperature of 65°C. After the reaction, the particles were washed with deionized water to pH 7 and dried (90°C, 4 hours). The dried particles were placed in an ethanol solution containing APTESS and GPTESS (2% concentration) at a ratio of 2:1, and reacted for 50 minutes at a temperature of 75°C. They were washed and set aside.

[0032] Preparation of functionalized polyethylene: 90 parts of low-density polyethylene, 4 parts of maleic anhydride and 0.6 parts of dicumyl peroxide were mixed, the reaction temperature was set at 190°C, the stirring speed was 35 rpm, and the reaction time was 10 minutes. After the reaction, the mixture was cooled and granulated.

[0033] Composite Mixing: Ingredients: 65 parts of high-density polyethylene, 9 parts of functionalized polyethylene, 10 parts of modified silicon carbide particles, 6 parts of modified alumina particles, 1.2 parts of silane coupling agent, 0.2 parts of heat stabilizer, 0.3 parts of antioxidant, and 0.5 parts of polyethylene glycol.

[0034] After mixing, the materials were placed in an extruder with a melt temperature of 190°C to 220°C, a screw speed of 250 rpm, and a mixing time of 8 minutes.

[0035] Tube forming: Co-extrusion three-layer structure: inner layer thickness 1.5mm, middle layer thickness 2.0mm, outer layer thickness 1.0mm. Extrusion pressure 18MPa, mold temperature 210℃, cooling water temperature 15℃. Cut after cooling for 20 minutes.

[0036] Example 3: Preparation of a high-performance wear-resistant and corrosion-resistant composite pipe.

[0037] Particle handling: Mix micron silicon carbide (3μm) and aluminum oxide (0.8μm) in a ratio of 3:1, add to 5% nitric acid solution and react for 15 minutes at 55°C. Then filter, wash with deionized water until neutral, and dry at 80°C for 4 hours. The treated particles are placed in a mixed solution of APTESS and GPTESS at a concentration of 1.8%, at a reaction temperature of 70°C, and for 35 minutes. Wash and dry for later use.

[0038] Preparation of functionalized polyethylene: 95 parts of high-density polyethylene, 3 parts of maleic anhydride and 1 part of diisopropylbenzene peroxide were melted and reacted in an internal mixer at a temperature of 175°C, a speed of 50 rpm and a reaction time of 10 minutes. After cooling, pellets were prepared.

[0039] Compounding process: Ingredients: 68 parts of high-density polyethylene, 7 parts of functionalized polyethylene, 12 parts of modified silicon carbide particles, 4 parts of alumina particles, 1.4 parts of silane coupling agent, 0.2 parts of heat stabilizer, 0.3 parts of antioxidant, and 0.6 parts of polyethylene glycol.

[0040] The mixture was mixed in a twin-screw extruder at a temperature range of 195°C to 225°C, a screw speed of 240 rpm, and a residence time of 9 minutes.

[0041] Extrusion molding: The multi-layer co-extrusion equipment was used to prepare a three-layer structure: inner layer thickness 1.0 mm (particle content 15%), middle layer thickness 2.5 mm (particle content 8%), outer layer thickness 1.2 mm (pure polyethylene). The extrusion pressure was 20 MPa, the mold temperature was 220°C, the cooling tank temperature was 18°C, and the cooling time was 15 minutes before cutting.

[0042] Example 4: Preparation of a highly wear-resistant composite pipe.

[0043] Particle pretreatment: Silicon carbide particles (particle size 2 μm) were treated with 5% dilute nitric acid solution for 20 minutes at 60°C, then filtered, washed and dried (85°C for 3 hours). They were then treated with 1.5% APTESS solution for 40 minutes at 75°C, and dried for later use.

[0044] Composite material ingredients: Ingredients: 70 parts of high-density polyethylene, 6 parts of functionalized polyethylene, 14 parts of modified silicon carbide particles, 5 parts of modified alumina particles, 1.5 parts of silane coupling agent, 0.3 parts of heat stabilizer, 0.4 parts of antioxidant, and 0.5 parts of dispersant.

[0045] Mixing and molding: The melt mixing temperature is 200℃~230℃, the screw speed is 220rpm, and the mixing time is 7 minutes. Then extrusion molding is carried out, and the inner layer thickness of the three-layer structure is 1.2mm, the middle layer thickness is 2.5mm, and the outer layer thickness is 0.8mm. The extrusion pressure is 15MPa, and the cooling time is 15 minutes before cutting.

[0046] Example 5: A multifunctional explosion-proof and environmentally friendly pipe.

[0047] Functionalized Polyethylene: 92 parts of high-density polyethylene, 4 parts of maleic anhydride, 0.8 parts of dicumyl peroxide, reaction temperature 185°C, stirring speed 45 rpm, reaction time 10 minutes. Cool and granulate for later use.

[0048] Composite material melt compounding: Ingredients: 60 parts high-density polyethylene, 10 parts functionalized polyethylene, 10 parts modified silicon carbide, 5 parts modified alumina, 1.5 parts Silane coupling agent, 0.3 parts of heat stabilizer, 0.3 parts of antioxidant, 0.7 parts of polyethylene glycol.

[0049] The melt temperature is 195°C to 220°C, the screw speed is 230 rpm, and the residence time is 6 minutes.

[0050] Extrusion molding: The thickness of the inner layer is 1.5 mm, the thickness of the middle layer is 2.0 mm, and the thickness of the outer layer is 1.0 mm. The extrusion pressure is 18 MPa, the mold temperature is 210°C, the cooling water tank temperature is 20°C, and the cutting is performed after 15 minutes.

[0051] A variety of comparative examples are designed below, each of which is based on the changes of the aforementioned embodiments and is compared around multiple innovative points of the invention to highlight the creativity of the present invention. Each comparative example discloses its specific preparation process and clearly describes the comparative technical solution and its key differences from the embodiments.

[0052] Comparative Example 1 (corresponding to Example 1) Comparison content: The multifunctional treatment on the particle surface is cancelled and only a simple activation treatment is performed.

[0053] Particle handling: Silicon carbide particles (a 4:1 mixture of micron and nanoparticles) were directly treated with 5% nitric acid solution for 20 minutes at 60°C, then washed with deionized water until neutral, and dried at 80°C for 3 hours. After treatment, no silane coupling modification was performed and the subsequent steps were directly added.

[0054] Preparation of functionalized polyethylene: According to the steps of Example 1, 95 parts of high-density polyethylene, 3 parts of maleic anhydride and 0.8 parts of diisopropylbenzene peroxide were used to prepare functionalized polyethylene.

[0055] Composite blending: The formulation was the same as that in Example 1, with a melt blending temperature of 190° C. to 230° C., a screw speed of 220 rpm, and a residence time of 7 minutes.

[0056] Extrusion molding: A multi-layer co-extrusion device was used, and the thickness of the inner layer, the reinforcing layer and the outer layer were the same as those in Example 1. The extrusion pressure was 16 MPa, and the cooling water tank temperature was 20°C.

[0057] Comparative Example 2 (corresponding to Example 2) Comparison content: Instead of using functionalized polyethylene, ordinary high-density polyethylene is used directly.

[0058] Particle modification: The alumina particles were treated with a 5% sodium hydroxide solution at 65°C for 25 minutes, washed until neutral and dried. They were then treated with a 1.5% ethanol solution of APTESS and GPTESS at 70°C for 40 minutes. The particle treatment was the same as in Example 2.

[0059] Composite blending: Ingredients: 74 parts of high-density polyethylene (without functionalization treatment), 12 parts of modified silicon carbide particles, 5 parts of modified alumina particles, 1.5 parts of silane coupling agent, 0.3 parts of heat stabilizer, 0.3 parts of antioxidant, and 0.5 parts of polyethylene glycol.

[0060] The melting temperature is 190°C to 220°C, the screw speed is 250 rpm, and the mixing time is 8 minutes.

[0061] Extrusion molding: The pipe structure and extrusion conditions are consistent with those in Example 2.

[0062] Comparative Example 3 (corresponding to Example 3) Comparison content: Eliminate nanoparticles and use only micron-sized reinforcement particles.

[0063] Particle handling: Silicon carbide particles (particle size 2 μm to 5 μm) and aluminum oxide particles (particle size 0.5 μm to 1 μm) were activated with 5% nitric acid and 5% sodium hydroxide solution, respectively, and the activation conditions were the same as those in Example 3. After treatment, the particles only contained micron-sized particles, and no nanoparticles were added. The subsequent silane coupling modification steps were the same as those in Example 3.

[0064] Preparation of functionalized polyethylene: Functionalized polyethylene was prepared according to the procedure of Example 3.

[0065] Composite blending: Ingredients: 68 parts of high-density polyethylene, 7 parts of functionalized polyethylene, 14 parts of modified silicon carbide particles (all micron-sized), 5 parts of modified alumina particles, 1.5 parts of silane coupling agent, 0.3 parts of heat stabilizer, 0.3 parts of antioxidant, and 0.6 parts of polyethylene glycol.

[0066] The melt temperature is 195°C to 225°C, the screw speed is 240 rpm, and the residence time is 9 minutes.

[0067] Extrusion molding: The tube thickness and forming process are the same as those in Example 3.

[0068] Comparative Example 4 (corresponding to Example 4) Comparison content: Cancel the multi-layer co-extrusion structure and adopt single-layer pipe.

[0069] Particle handling: Silicon carbide particles (particle size 1 μm to 3 μm) were treated with 5% nitric acid solution for 20 minutes, and the subsequent APTESS modification steps were the same as those in Example 4.

[0070] Preparation of functionalized polyethylene: Functionalized polyethylene was prepared according to the procedure of Example 4.

[0071] Composite blending: Ingredients: 70 parts of high-density polyethylene, 6 parts of functionalized polyethylene, 14 parts of modified silicon carbide particles, 5 parts of modified alumina particles, 1.5 parts of silane coupling agent, 0.3 parts of heat stabilizer, 0.4 parts of antioxidant, and 0.5 parts of dispersant.

[0072] The melt blending temperature was 200° C. to 230° C., the screw speed was 220 rpm, and the mixing time was 7 minutes.

[0073] Extrusion molding: The composite material was extruded into a single-layer tube with a thickness of 3.5 mm using a single-layer extrusion device, an extrusion pressure of 15 MPa, and a cooling time of 15 minutes.

[0074] Comparative Example 5 (corresponding to Example 5) Comparison content: No multifunctional silane coupling agent is used, only a single coupling agent is used.

[0075] Particle modification: The silicon carbide particles and the aluminum oxide particles were activated with dilute nitric acid or sodium hydroxide solution, the conditions being the same as in Example 5. They were then treated with a 1.5% ethanol solution of APTESS at 70° C. for 40 minutes. GPTESS was not used.

[0076] Preparation of functionalized polyethylene: The preparation process of functionalized polyethylene is consistent with that of Example 5.

[0077] Composite blending: Ingredients: 65 parts of high-density polyethylene, 10 parts of functionalized polyethylene, 12 parts of modified silicon carbide particles, 5 parts of modified alumina particles, 1.0 part of APTESS, 0.3 parts of heat stabilizer, 0.3 parts of antioxidant, and 0.7 parts of polyethylene glycol.

[0078] The melt temperature is 195°C to 220°C, the screw speed is 230 rpm, and the residence time is 6 minutes.

[0079] Extrusion molding: The thickness and forming process of the multi-layer structure of the tube are consistent with those of Example 5.

[0080] In order to verify the technical effect of the present invention, a single factor comparative experimental design was adopted to compare the embodiments with the corresponding comparative examples, and the superiority of the present invention was fully demonstrated by testing key properties such as wear resistance, interface bonding strength, acid and alkali resistance, and explosion-proof performance. The following is a specific experimental design and test method.

[0081] Experiment 1: Effect of particle surface multifunctionalization on wear resistance.

[0082] Experimental objective: To verify the effect of multifunctional modification of particle surface (APTESS and GPTESS) on improving wear resistance.

[0083] Experimental samples: Example 1: Particles modified with APTESS and GPTESS.

[0084] Comparative Example 1: The particles were only activated with dilute nitric acid without any coupling agent modification.

[0085] Experimental methods: Test standard: According to ASTM G65 standard (dry sand rubber wear test), the wear volume of the sample is tested under a load of 50N.

[0086] Test setup: Use a dry sand rubber wear tester, with sand particle size of 0.25mm to 0.5mm, sliding distance of 2000m, and rotation speed of 300rpm.

[0087] Test sample size: 50mm×50mm×3mm slice sample, sampled from the inner layer of the pipe.

[0088] Data recording: Each sample was tested 3 times, the wear volume was recorded, and the average value was taken.

[0089] Experiment 2: Effect of functionalized polyethylene on interfacial bonding strength Experimental objective: To verify the effect of introducing functionalized polyethylene on enhancing the particle-matrix interface bonding strength.

[0090] Experimental samples: Example 2: Composite material containing functionalized polyethylene.

[0091] Comparative Example 2: does not contain functionalized polyethylene, and the matrix is ​​ordinary high-density polyethylene.

[0092] Experimental methods: Test standard: According to ASTM D4541 standard (adhesion pull-off test), the interfacial bonding strength between particles and substrate is tested.

[0093] Test setup: After the inner layer of the pipe sample is coated with glue, it is adhered to the aluminum plate. A pulling force is gradually applied using a pulling machine, and the maximum load at which the interface bonding force breaks is recorded.

[0094] Sample processing: Cut 20mm×20mm×3mm samples and perform pull-out tests on them respectively. Repeat the test 5 times for each group.

[0095] Experiment 3: Effect of multi-scale particle synergistic enhancement on pressure resistance Experimental objective: To verify the contribution of the coordinated distribution of nanoparticles and micron particles to the pressure resistance of the material.

[0096] Experimental samples: Example 3: Micron particles and nanoparticles are mixed and distributed in a ratio of 4:1.

[0097] Comparative Example 3: Contains only micron particles without nanoparticles.

[0098] Experimental methods: Test standard: According to ISO1167 standard (hydrostatic pressure resistance test of plastic pipes), the pressure bearing capacity of pipes under constant water pressure is tested.

[0099] Test settings: The pressure of the internal pressure test machine is 10MPa, the water temperature is 60℃, the test time lasts until the pipe ruptures, and the rupture time and pressure are recorded.

[0100] Test samples: Take 3 sections of 50mm long pipe samples from each group and take the average value.

[0101] Experiment 4: Contribution of multilayer structure to acid and alkali resistance Experimental objective: To verify the corrosion resistance of multi-layer co-extruded structures in strong acid and strong alkali environments.

[0102] Experimental samples: Embodiment 4: three-layer co-extrusion structure.

[0103] Comparative Example 4: Single-layer composite pipe.

[0104] Experimental methods: Test standard: According to ISO175 standard (plastic chemical resistance test), the mass change rate of the sample in acid and alkali solution is measured.

[0105] Test setup: The sample was immersed in a sulfuric acid solution with a pH of 2 and a sodium hydroxide solution with a pH of 12 at a temperature of 60°C for 7 days. The sample mass change rate and surface integrity were recorded.

[0106] Sample processing: Cut 20mm×20mm×3mm samples and conduct acid and alkali immersion experiments respectively, with each group repeated 3 times.

[0107] Experiment 5: Effects of monofunctional and multifunctional coupling agents on particle interfaces Experimental objective: To verify the differences in interfacial bonding performance between multifunctional coupling agents (APTESS and GPTESS) and a single coupling agent (APTESS).

[0108] Experimental samples: Example 5: Particles modified with bifunctional coupling agents APTESS and GPTESS.

[0109] Comparative Example 5: The particles were modified only with APTESS monofunctional coupling agent.

[0110] Experimental methods: Test standard: According to ASTM D638 standard (tensile test), the tensile strength of the pipe is tested.

[0111] Test setup: Use a universal material testing machine with a tensile speed of 5 mm / min and record the maximum tensile load.

[0112] Sample size: dumbbell-shaped sample of 50mm×10mm×3mm, sampled from the middle layer of the pipe. Each group was tested 3 times.

[0113] Experiment 6: Effect of multifunctional particle distribution on explosion-proof performance Experimental objective: To verify the contribution of particle distribution and interface bonding properties to the explosion-proof capability of materials.

[0114] Experimental samples: Example 1: Particles modified with APTESS and GPTESS are evenly distributed.

[0115] Comparative Example 1: The particles were only activated without modification with a coupling agent.

[0116] Experimental methods: Test standard: According to IEC61340 standard (static accumulation and release test), the surface resistance and static discharge capacity of the pipe are measured.

[0117] Test setup: Use a surface resistance tester, voltage 10V, record the surface resistance value (Ω).

[0118] Sample processing: Cut a 30mm×30mm surface sample, test it 5 times, and take the average value.

[0119] In order to verify the technical effect of the present invention, a single factor comparative experimental design was adopted to compare the embodiments with the corresponding comparative examples, and the superiority of the present invention was fully demonstrated by testing key properties such as wear resistance, interface bonding strength, acid and alkali resistance, and explosion-proof performance. The following is a specific experimental design and test method.

[0120] Experiment 1: Effect of particle surface multifunctionality on wear resistance Experimental description: Experimental objectives: The improvement effect of the multifunctionalization of the particle surface (modification with bifunctional coupling agents APTESS and GPTESS) on the wear resistance of the composite material was verified, and the performance difference between Example 1 and Comparative Example 1 was compared.

[0121] Experimental samples: Example 1: Particles modified with bifunctional coupling agents APTESS and GPTESS.

[0122] Comparative Example 1: The particles were only activated with dilute nitric acid without any coupling agent modification.

[0123] Experimental equipment and standards: Test equipment: dry sand rubber wear tester.

[0124] Test standard: ASTM G65 standard (dry sand rubber wear test).

[0125] Experimental steps: Sample preparation: Inner layer samples of 50 mm×50 mm×3 mm were cut from the pipes of Example 1 and Comparative Example 1, respectively.

[0126] Prepare 3 parallel samples for each group and mark them with numbers.

[0127] Wear test: Wear medium: quartz sand (particle size 0.25mm~0.5mm).

[0128] Load: 50N.

[0129] Sliding distance: 2000m.

[0130] Rotation speed: 300rpm.

[0131] Fix the sample on the sample stage of the testing machine, run the test under the set parameters, and record the wear volume.

[0132] Data Records: An electronic balance was used to record the sample mass before and after each test and to calculate the wear volume.

[0133] Each sample was tested 3 times, and the average value was taken and recorded.

[0134] Experimental data: Table 1.1 Wear test data of Example 1 and Comparative Example 1 Experimental summary: After the particle surface was modified by APTESS and GPTESS bifunctional coupling agents, the interfacial bonding force between the particle surface and the matrix was significantly enhanced, and the result was that the wear volume of Example 1 was significantly lower than that of Comparative Example 1. APTESS and GPTESS respectively provided amino and epoxy groups, which introduced multi-point chemical bonding on the particle surface, improving the fixation effect of the particle in the matrix. Under the high shear conditions of dry sand friction, the stability of this chemical bond showed obvious advantages, inhibited the shedding of particles, and reduced material wear.

[0135] In addition, the synergistic effect of APTESS and GPTESS not only improves the bonding strength between the particle surface and the matrix interface, but also optimizes the distribution state of the particles. Combined with the above-mentioned mechanism analysis, the surface hydroxyl groups of the particles form a highly stable interface through silane coupling reaction, ensuring the effective embedding of the particles under stress conditions. This multifunctional design is obviously superior to the interface bonding method of simple physical adsorption, and significantly improves the wear resistance.

[0136] In contrast, since only surface activation treatment was performed in Comparative Example 1, the particles and the matrix mainly relied on weak physical interlocking. During the sliding friction process, particle shedding became the main wear mechanism, which directly led to a significant increase in the wear volume. It can be seen that the introduction of the multifunctional coupling agent not only improves the chemical bonding ability of the particles, but also optimizes the overall structural properties of the composite material through chemical reactions at the interface.

[0137] Experiment 2: Effect of functionalized polyethylene on interfacial bonding strength Experimental description: Experimental objectives: The effect of the introduction of functionalized polyethylene (F-PE) on the particle-matrix interface bonding strength was evaluated, and its role in improving the interface performance was verified by comparing Example 2 with Comparative Example 2.

[0138] Experimental samples: Example 2: Composite material containing functionalized polyethylene (F-PE).

[0139] Comparative Example 2: The substrate is ordinary high-density polyethylene (without functionalization treatment).

[0140] Experimental equipment and standards: Test equipment: Adhesion pull-off test machine.

[0141] Test standard: ASTM D4541 (adhesion pull-off test).

[0142] Experimental steps: Sample preparation: Samples were taken from the pipes of Example 2 and Comparative Example 2, cut into rectangular samples of 20 mm×20 mm×3 mm, and the test surfaces were polished with sandpaper and cleaned.

[0143] Apply industrial adhesive (epoxy resin glue) on the surface of the sample, bond it to the aluminum plate, and wait for the glue to cure. The curing time is set to 24 hours and the temperature is controlled at 25°C.

[0144] Adhesion test: Fix the sample on the fixture of the tensile testing machine, load it slowly, and record the maximum tensile force when the interface breaks.

[0145] The fracture modes were divided into two cases: particle shedding or matrix fracture, and the fracture characteristics were recorded.

[0146] Data Records: Each group of tests was performed 5 times, and the maximum pull-out load was recorded each time. The average value was taken and the failure mode was recorded.

[0147] Experimental data: Table 2.1 Interface bonding strength test data of Example 2 and Comparative Example 2: Experimental summary: The introduction of functionalized polyethylene significantly enhances the interfacial bonding performance between the particles and the matrix. Experiments show that the pull-out strength of Example 2 is much higher than that of Comparative Example 2. This difference stems from the chemical activity of the carboxyl group in the functionalized polyethylene, which covalently reacts with the amino or epoxy groups on the surface of the particles at the interface to form a strong chemical bond. In contrast, the ordinary polyethylene matrix of Comparative Example 2 lacks chemical activity, and the interfacial bonding between the particles and the matrix relies only on weak physical intercalation, so the particles are easy to fall off after loading.

[0148] Combined with the mechanism analysis, the functionalized polyethylene not only achieves chemical fixation of particles through carboxyl groups, but also improves the dispersion state of particles during processing, making the interface more uniform. The combined effect of this chemical bond and physical intercalation significantly improves the stress transfer capacity of the interface. During the loading process, the energy dissipation at the interface is mainly achieved by chemical bond breaking, rather than simple particle shedding, which explains the higher pull-out strength of Example 2.

[0149] In contrast, in Comparative Example 2, due to the lack of chemical bonding between the particles and the matrix, the fracture is mainly manifested as the particles detaching from the matrix, and the load concentration at the interface leads to a significant decrease in the pull-out strength. The experimental results clearly prove that functionalized polyethylene not only optimizes the interfacial bonding force, but also significantly improves the overall interfacial performance stability of the composite material. Experiment 3: Effect of multi-scale particle synergistic enhancement on pressure resistance Experimental description: Experimental objectives: By comparing Example 3 with Comparative Example 3, the effect of the coordinated distribution of multi-scale particles (micrometer and nanometer particles) in improving the pressure resistance of the pipe is verified, and the contribution of particle size and distribution to the structural performance of the pipe is discussed.

[0150] Experimental samples: Example 3: Micron particles and nanoparticles are mixed and distributed in a ratio of 4:1.

[0151] Comparative Example 3: Only micron particles (particle size 2-5 μm) were used without nanoparticles.

[0152] Experimental equipment and standards: Test equipment: Plastic pipe hydrostatic pressure tester.

[0153] Test standard: ISO1167 (test on hydrostatic pressure resistance of plastic pipes).

[0154] Experimental steps: Sample preparation: 50 mm long samples were cut from the pipes prepared in Example 3 and Comparative Example 3, respectively. A total of 6 sections were sampled, and 3 sections in each group were used for testing.

[0155] Sealed joints are installed at both ends of the sample to ensure no leakage during the water pressure test.

[0156] Test conditions: Place the sample in a hydrostatic pressure tester, fill it with clean water, and gradually increase the pressure to 10MPa.

[0157] Control the water temperature at 60℃ and maintain a constant water pressure until the pipe ruptures, and record the rupture time and pressure value.

[0158] Observe the rupture form of the pipe (inner layer peeling, outer layer rupture or overall rupture).

[0159] Data Records: Each group of samples was tested three times, the pressure and rupture time were recorded, the average value was calculated and the rupture characteristics were analyzed.

[0160] Experimental data: Table 3.1 Hydrostatic pressure resistance test data of pipes in Example 3 and Comparative Example 3 Experimental summary: The coordinated distribution of multi-scale particles obviously plays a decisive role in improving the pressure resistance of the pipe. The addition of nanoparticles in Example 3 not only fills the gaps between the distribution of micron particles, but also significantly optimizes the overall structural uniformity of the composite material. Under high pressure conditions, nanoparticles fill the interface gaps, slow down the stress concentration effect, prolong the rupture time of the material, and significantly increase the rupture pressure. It can be observed that the rupture of the pipe in Example 3 is an overall rupture rather than interlayer peeling, which directly indicates the improvement of the interface bonding strength and the overall bearing capacity.

[0161] In contrast, in Comparative Example 3, only micron particles were used, the interface gaps were large, and the mechanical support between the particles could not evenly transfer stress. Under high pressure, the micron particles could not effectively prevent the rapid expansion of cracks, resulting in a significant reduction in the rupture time and pressure of the pipe. The rupture form was mainly inner layer peeling or local disintegration. This failure mode reflects the problems of uneven particle distribution and insufficient interface bonding.

[0162] The introduction of nanoparticles also enhances the pipe's ability to resist damage. From a mechanistic point of view, the nanoparticles form a stable dissipative structure at the interface through chemical bonding and physical intercalation with the matrix. This microscopic enhancement mechanism provides the material with a higher energy absorption capacity when subjected to external forces, allowing the pipe to withstand higher internal pressures. The results show that multi-scale particle distribution is indispensable for the optimization of the structural performance of composite materials, and its effect is better than that of a single particle reinforcement design.

[0163] Experiment 4: Contribution of multilayer structure to acid and alkali resistance Experimental description: Experimental objectives: The effect of the multi-layer co-extrusion structure on improving the chemical corrosion resistance of the composite material in an acidic and alkaline environment was verified, and the stability and corrosion resistance of the material under extreme acidic and alkaline conditions were evaluated by comparing Example 4 with Comparative Example 4.

[0164] Experimental samples: Embodiment 4: Three-layer co-extruded composite structure pipe.

[0165] Comparative Example 4: Single-layer composite pipe.

[0166] Experimental equipment and standards Test equipment: acid and alkali immersion test tank, high-precision electronic balance.

[0167] Test standard: ISO175 standard (plastic chemical resistance test).

[0168] Experimental steps: Sample preparation: Samples of 20 mm×20 mm×3 mm were cut from the pipes of Example 4 and Comparative Example 4, and three parallel samples were prepared for each group and marked with numbers.

[0169] Each sample was lightly sanded at the edge with sandpaper, the surface was cleaned, and dried for later use.

[0170] Soak test: Acidic solution: 10% sulfuric acid solution, pH 2; alkaline solution: 10% sodium hydroxide solution, pH 12.

[0171] The samples were immersed in two solutions respectively, the solution temperature was controlled at 60°C, and the immersion time was set to 7 days.

[0172] Observe the surface condition of the samples daily and record any obvious cracks, discoloration, or peeling.

[0173] Quality change test: Before and after immersion, the sample mass was recorded using a high-precision electronic balance, and the mass change rate (△m%) was calculated.

[0174] Each sample was measured 3 times and the average value was taken.

[0175] Experimental data: Table 4.1 Acid-base immersion test data of Example 4 and Comparative Example 4 Experimental summary: The experimental results clearly show that the multilayer structure performs much better than a single layer of material in extreme acid and alkali environments. The three-layer design of Example 4 effectively divides the work, where the inner layer material enhances chemical resistance through high particle content, the middle layer buffers the erosion pressure of acid and alkali media, and the outer layer provides an additional protective barrier. This layered design avoids the concentrated destruction of a single layer of material under acid and alkali erosion, and significantly improves the overall corrosion resistance.

[0176] From a mechanistic point of view, the multi-layer structure makes the chemical erosion process slow and dispersed. When the acid-base medium first contacts the outer layer, the outer layer of polyethylene provides initial barrier through its low water absorption and high density. Subsequently, the high-strength interface formed by the functionalized polyethylene in the middle layer combined with the particles further slows down the penetration rate of the acid-base medium and enhances the overall chemical tolerance. This synergistic mechanism of blocking-buffering-protection greatly reduces the mass loss rate of the material in extreme environments.

[0177] In contrast, the single-layer material of Comparative Example 4 showed obvious local damage under acid-base conditions. The appearance of edge peeling and cracks indicates that the acid-base medium directly acts on the internal material, resulting in local stress concentration and rapid degradation. It can also be seen from the experimental data that the mass change rate of Comparative Example 4 is significantly higher than that of Example 4, and the surface state is rougher. The main reason for this degradation is that the single-layer material cannot effectively disperse the chemical erosion pressure, and the overall structure lacks targeted design, which directly leads to unstable performance. The effect and superiority of the multi-layer co-extrusion design have therefore been fully verified.

[0178] Experiment 5: Effects of multifunctional and monofunctional coupling agents on particle interface bonding.

[0179] Experimental description: Experimental objectives: The effects of APTESS (monofunctional coupling agent) and APTESS+GPTESS (bifunctional coupling agent) in the particle modification process were compared, and the improvement effect of the bifunctional coupling agent on the interface bonding and tensile properties of the composite materials was evaluated.

[0180] Experimental samples: Example 5: Particles modified with bifunctional coupling agents APTESS and GPTESS.

[0181] Comparative Example 5: The particles were modified only by the APTESS monofunctional coupling agent.

[0182] Experimental equipment and standards: Testing equipment: universal material testing machine.

[0183] Test standard: ASTM D638 (plastic tensile properties test).

[0184] Experimental steps: Sample preparation: Dumbbell-shaped samples (size: 50 mm×10 mm×3 mm) were cut from the pipes prepared in Example 5 and Comparative Example 5, and the surfaces were polished with sandpaper to ensure smoothness without any traces of machining.

[0185] Prepare 6 samples in each group for repeated testing and mark them with numbers.

[0186] Tensile test: The sample was fixed on the fixture of the universal material testing machine and the initial length was tested (the gauge length was 25 mm).

[0187] Set the stretching speed to 5 mm / min, gradually increase the load, and record the maximum tensile stress (unit: MPa) when the sample breaks.

[0188] The fracture form of the sample was recorded and classified into particle shedding type interface failure or matrix fracture type overall failure.

[0189] Data Records: Each sample was tested repeatedly, the maximum tensile stress was recorded, and the average value was calculated.

[0190] Experimental data: Table 5.1 Tensile performance test data of Example 5 and Comparative Example 5 Experimental summary: The advantages of the bifunctional coupling agents of APTESS and GPTESS in interface modification are very significant in the experimental results. The maximum tensile stress of Example 5 is significantly higher than that of Comparative Example 5. The bifunctional coupling agent provides a multi-point bonding interface enhancement effect. The amino group of APTESS chemically bonds with the particle surface, while the epoxy group provided by GPTESS further participates in the reaction with the matrix. This dual bonding mechanism establishes a high-strength particle-matrix interface, which significantly reduces the possibility of interface damage.

[0191] From the perspective of mechanism analysis, the bifunctional coupling agent not only strengthens the chemical reactivity of the particle surface, but also improves the transmission efficiency of stress at the interface. Especially under the action of external force, the interface bonding is more stable, which significantly improves the tensile properties of the entire material. The damage form in Example 5 is mainly manifested as overall damage of matrix fracture type, rather than local damage of particle shedding type, which further illustrates the supporting role of the enhancement of interface bonding force on the overall performance of the material.

[0192] In contrast, Comparative Example 5 only uses APTESS as a monofunctional coupling agent, and the interface bonding mainly relies on a single amino reaction. Although the interface performance is improved to a certain extent, there are fewer bonding points between the particles and the matrix, which easily forms stress concentration during loading, leading to interface damage. The low tensile strength and particle shedding type failure form in the experiment just reflect this deficiency. The introduction of a bifunctional coupling agent not only achieves comprehensive optimization of interface performance, but also provides reliable protection for the structural stability of the composite material.

[0193] Experiment 6: Effect of multifunctional particle distribution on explosion-proof performance.

[0194] Experimental description: Experimental objectives: The effects of particle surface modification and uniform distribution on the explosion-proof performance of the material were evaluated, and the effect of the introduction of APTESS and GPTESS bifunctional coupling agents on the surface resistance performance of the material was verified by comparing Example 1 with Comparative Example 1.

[0195] Experimental samples: Example 1: Particles are modified with bifunctional coupling agents APTESS and GPTESS and uniformly distributed in the matrix.

[0196] Comparative Example 1: The particles were only activated by an acidic solution without any coupling agent modification, and the particles were unevenly distributed.

[0197] Experimental equipment and standards: Test equipment: surface resistance tester (model: Megaohmmeter6521).

[0198] Test standard: IEC61340 standard (static accumulation and release test).

[0199] Experimental steps: Sample preparation: 30 mm×30 mm thin slice samples were cut from the pipes of Example 1 and Comparative Example 1, and there were no obvious scratches or impurities on the surface.

[0200] Prepare 3 parallel samples for each group and mark them with numbers.

[0201] Surface resistance test: Before testing, the samples were placed in an environment of 25°C and 50% humidity for 24 hours for equilibrium treatment.

[0202] The sample was placed between the test electrodes of the surface resistance tester and the test voltage was set to 10V.

[0203] At the beginning of the test, each sample was kept in contact with the electrode for 10 seconds, and the resistance value (unit: Ω) was recorded.

[0204] Data Records: Each sample was tested 3 times and the average value was recorded.

[0205] Experimental data: Table 6.1 Surface resistance test data of Example 1 and Comparative Example 1 Experimental summary: The surface resistance value of Example 1 is significantly lower than that of Comparative Example 1. This difference is due to the combined effect of particle surface modification and distribution uniformity. The bifunctional coupling agents APTESS and GPTESS provide a variety of chemical groups on the particle surface, enabling the particles to form a stable chemical bond with the functionalized polyethylene matrix. Through the intermolecular bonding, the particles are more evenly distributed, forming a continuous conductive path, which effectively reduces the resistance value of the material surface. In the process of electrostatic discharge, this structure avoids the risk of local charge accumulation and greatly improves the explosion-proof performance of the material.

[0206] The surface activity of the particles directly affects the conductive properties. In Comparative Example 1, since the particles were only activated by an acidic solution, the surface lacked sufficient chemical reactivity and was fixed to the matrix only by physical intercalation. During the test, the particles tended to agglomerate in the matrix and could not form an effective conductive network, resulting in a significant increase in the surface resistance. The reduction in electrostatic discharge efficiency further exacerbated the risk of failure of the material in a high charge accumulation environment.

[0207] From a mechanistic point of view, the synergistic effect of APTESS and GPTESS not only enhances the interfacial bonding ability of the particles, but also improves their dispersion state in the matrix, forming more electron transfer channels. This modification mechanism ensures the reliability of the composite material during electrostatic discharge by optimizing particle distribution and interface stability. The experimental results show that the introduction of bifunctional coupling agents is crucial to the explosion-proof performance of the composite material, and its effect is far better than traditional particle modification methods.

[0208] Summarize: It can be seen from the experimental results that Example 1 shows significant advantages in the explosion-proof performance test. This advantage does not simply come from the presence of particles, but is determined by the chemical bonding formed after the modification of the bifunctional coupling agents APTESS and GPTESS. The bifunctional groups establish multi-point connections between the particles and the matrix, which not only enhances the interfacial bonding force, but also improves the dispersion state of the particles in the matrix, and finally constructs a continuous and stable conductive path. These characteristics are particularly critical in high-voltage electrostatic testing because they directly determine the electrostatic discharge efficiency of the material.

[0209] The performance of Comparative Example 1 is significantly inferior. The particles are only activated by an acidic solution, and the surface reactivity is low, making it difficult to form a chemical bond with the matrix. During processing, these particles tend to agglomerate, resulting in a discontinuous conductive path of the composite material. This particle agglomeration leads to a higher surface resistance value and limits the material's ability to conduct static electricity. In a high static electricity accumulation environment, such a material is more prone to local charge accumulation, which directly increases the possibility of explosion-proof failure.

[0210] The introduction of APTESS and GPTESS not only provides chemical enhancement in terms of interface bonding, but also improves the physical properties of the particles through nanoscale distribution. The particles are tightly bonded to the matrix through bonding, avoiding common failure modes such as particle shedding and interface separation. This distribution characteristic is obviously the core technical point for optimizing the explosion-proof performance of materials, and it is also an advantage that is difficult to achieve with traditional modification methods. The experimental data fully proves the value of bifunctional coupling agents and their irreplaceable role in optimizing the performance of composite materials.

[0211] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe, characterized in that: Made from the following components in parts by mass: High-density polyethylene: 60 to 75 parts; Functionalized polyethylene: 5 to 10 parts; Silicon carbide particles: 8 to 15 parts; Alumina particles: 3 to 8 parts; Silane coupling agent: 1 to 2 parts; Heat stabilizer: 0.1 to 0.3 parts; Antioxidant: 0.2 to 0.5 parts; Dispersant: 0.5 to 1 part.

2. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 1 is characterized in that: The functionalized polyethylene is prepared by the following method: polyethylene and maleic anhydride are mixed in a mass ratio of 90-95:2-4, an initiator is added in an amount of 0.5%-1% by mass, a grafting reaction is carried out at 170° C.-200° C., the reaction time is 8 minutes-15 minutes, and then the mixture is cooled and granulated.

3. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 1 is characterized in that: The silicon carbide particles include micron particles with a particle size of 1 μm to 5 μm and nano particles with a particle size of 50 nm to 100 nm, which are mixed in a mass ratio of 4:

1.

4. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 1 is characterized in that: The aluminum oxide particles have a particle size range of 0.5 μm to 1 μm, and are surface treated after being activated by dilute nitric acid or sodium hydroxide solution.

5. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 1, characterized in that: The silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltriethoxysilane, which are used in a mass ratio of 1:

1.

6. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 1, characterized in that: The high-density polyethylene, functionalized polyethylene, silicon carbide particles, alumina particles, silane coupling agent and additives are mixed in the mass fraction ratio and melt-blended in a twin-screw extruder. The melting temperature is 190° C. to 230° C., the screw speed is 200 rpm to 250 rpm, and the residence time is 6 minutes to 10 minutes.

7. The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe according to claim 6, characterized in that: The mixed materials are formed by multi-layer co-extrusion, and the PE pipe has a three-layer structure, including: Inner layer: 1.0mm-1.5mm thick, composed of a mixture with a reinforcing particle content of 15%; Middle layer: 2.0mm to 3.0mm thick, composed of a mixture of functionalized polyethylene and reinforced particles; Outer layer: 0.8mm~1.5mm thick, made of high-density polyethylene.

8. The wear-resistant, acid-corrosion-resistant, environmentally friendly explosion-proof PE pipe according to claim 7, characterized in that: During the extrusion process of the three-layer structure material, the extrusion pressure is 10MPa-20MPa, the mold temperature is 200°C-240°C, and the cooling water tank temperature is 15°C-25°C.

9. The wear-resistant, acid-corrosion-resistant, environmentally friendly explosion-proof PE pipe according to claim 1, characterized in that: The surface modification of the reinforcing particles comprises the following steps: S1. Treat the reinforced particles with a dilute acid or alkaline solution to activate the particle surface and remove impurities at a temperature of 50°C to 70°C for 15 to 30 minutes; S2. Introduce bifunctional groups on the particle surface through a coupling agent, the coupling agent concentration is 1.0% to 2.0%, the reaction temperature is 60°C to 80°C, and the reaction time is 30 minutes to 60 minutes.

10. A method for preparing an environmentally friendly explosion-proof PE pipe that is wear-resistant and acid-corrosion-resistant, characterized in that: The wear-resistant and acid-corrosion-resistant environmentally friendly explosion-proof PE pipe used in any one of claims 1 to 9 comprises the following steps: S1. After the silicon carbide particles and the aluminum oxide particles are surface activated, a silane coupling agent is added for modification to obtain surface modified particles; S2. grafting polyethylene with maleic anhydride under the action of an initiator to obtain functionalized polyethylene; S3. The high-density polyethylene, the functionalized polyethylene, the modified particles and the additives are mixed in a weight ratio and melt-blended in an extruder to obtain a composite material; S4. The composite material is extruded through a multi-layer co-extrusion device to form a three-layer structure, including an inner layer, a middle layer and an outer layer, and the PE pipe is obtained by cooling after extrusion.

Citation Information

Cited By

  • HDPE (high-density polyethylene) solid-wall tube based on carbon nanotubes and preparation method of HDPE solid-wall tube

    CN121182024A

  • Flame-retardant wear-resistant multi-layer polyethylene pipe and preparation method thereof

    CN121469065A

  • Flame-retardant wear-resistant multilayer polyethylene pipe and method for producing the same

    CN121469065B